The fluidity of Finnish youths’ Personal worldviews - Tuuli, Lipiäinen (International journal of children's spirituality, 2023)
This article aims to understand the personal worldviews of Finnish youths. The fluidity of young people’s personal worldviews has been highlighted in a number of previous studies, and this study presents more information by focusing on possible spiritual and religious elements in the personal worldviews of young people and on the influences that affect their personal worldviews. The data of this study consist of a quantitative questionnaire acquired from Finnish upper secondary school students (N = 973). The results show that young people’s personal worldviews are not fixed but are fluid and that nominal membership in a religious community does not explain their worldviews. Young people do not see religion as important to them, and they see religion more as a part of culture and their environment than as a part of their personal worldview. The most important sources of information for the construction of their personal worldview are school and the Internet.